If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5(a + 2) = 7 + a Reorder the terms: 5 + -5(2 + a) = 7 + a 5 + (2 * -5 + a * -5) = 7 + a 5 + (-10 + -5a) = 7 + a Combine like terms: 5 + -10 = -5 -5 + -5a = 7 + a Solving -5 + -5a = 7 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -5 + -5a + -1a = 7 + a + -1a Combine like terms: -5a + -1a = -6a -5 + -6a = 7 + a + -1a Combine like terms: a + -1a = 0 -5 + -6a = 7 + 0 -5 + -6a = 7 Add '5' to each side of the equation. -5 + 5 + -6a = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -6a = 7 + 5 -6a = 7 + 5 Combine like terms: 7 + 5 = 12 -6a = 12 Divide each side by '-6'. a = -2 Simplifying a = -2
| 6z^2+19z+10=0 | | x/(-2)=-61 | | (4x+1)(3x-2)=0 | | 3s-2=5s-6 | | -3r-13r=2 | | 5v^2+15v-50=0 | | 80-x=91 | | 16n+8=49n+67 | | x/(-4)=-34 | | 24*14=x(x+8) | | 24*10=8(8+x) | | 8+x=14+10 | | 8x=10*14 | | -270*x=-30 | | (7+6i)x(3+i)= | | 3(6x+9)-10x=1 | | 4y+2=0 | | 4x^2+8x+6=0 | | 3y-3=7y-1 | | -110+x=19 | | 4.5+3.4= | | 2(x+2)-9=4x-2(5+x) | | 5x=-x+18 | | 5x-(x-4)=24 | | -11(3.2)(.12(-12))= | | (7+6i)(3+i)= | | 2x+19=3x+2 | | 3x-10=-2x+28 | | -12t+20+8t=5t-9 | | (5+x)(4+x)(x+3)=420 | | 27=7+37t-16t^2 | | ((5+x)(4+x)(x+3))-420=0 |